(untitled) (The Himalayan Geographers, 2025)
Spring water resource is a natural source of freshwater that emerges to the land from the underground of the Earth has been a source of drinking water in the hilly region of Nepal. The Waling Municipality covers 128.4 square kilometers and comprises 14 wards located in the Syangja district, Nepal. The study applied a mixed method comprising quantitative and qualitative approaches, where the information was gathered through field observation and key informant interview with 14 individuals of respective wards having knowledge about water sources. The study provides the spatial distribution of the spring water resources using remote sensing and GIS tools. 73 permanent (perpetual for round the year) spring water resources have been identified in the Waling Municipality. The elevation range of 800–1100 meters exhibits the highest availability of spring water resources, containing 35 springs.